The dataset of multi-target vital signs monitored by FMCW radar - Lei, Guangyu; Cheng, Wei; Yin, Xipeng; Wu, Yuqing (Data in brief, 2024)
The dataset presents the raw data of respiration and heartbeat of two human subjects monitored by 60GHz Frequency-Modulated Continuous Wave (FMCW) radar and the validation data obtained by the electrocardiogram (ECG) front-end. During the radar-based vital signs monitoring, the subjects were simultaneously equipped with the ECG front-end, integrated with an Arduino board, to collect muscle electric signal waveforms, which enabled the estimation of the actual number of respirations and heartbeats of the subjects during the radar monitoring. To assess the impact of radar parameters, as well as the angle and distance between the subjects and the radar, on monitoring accuracy, the dataset classifies the positions of the human subjects within the scene into symmetric and asymmetric cases. Monitoring was conducted using various radar modulation bandwidths across different angles and distances in an open environment where only the human subjects were present. The objective of this dataset is to facilitate the development of a reliable system for monitoring multiple subjects' respiration and heartbeat using a single-view FMCW radar, emphasizing enhancing the radar's ability to distinguish between different targets and improving the accuracy of respiratory and heartbeat rate monitoring.